The hidden life of the pond - Schwartz, David M.; Kuhn, Dwight (New York : Crown Publishers, 1988)
Photographs and text introduce the animals, insects, and plants in a pond.
Keywords: Pond animals -- Juvenile literature; Pond plants -- Juvenile literature; Pond ecology -- Juvenile literature; Pond animals; Pond plants; Pond ecology; Ecology